A cross-sectional study of the relationships between organizational justices and OCB. Issue 6 (29th July 2014) - Kwon Choi, Byoung; Koo Moon, Hyoung; Ko, Wook; Min Kim, Kyoung
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to test the mediating effect of organizational identification (OI) in the relationship between organizational justice and organizational citizenship behavior (OCB), and also to examine the moderating effects of transactional and relational contracts in the relationship between OI and OCB. Design/methodology/approach – Data were collected from employees working for ten companies in South Korea. The participants were asked with a self-reported survey, and 284 questionnaires were used in the analyses. Findings – Among the three types of organizational justice, the effects of distributive and interactional justice on OCB were mediated by OI. The authors also found that the positive relationship between OI and OCB was stronger for both a low level of transactional and a high level of relational contract. In addition, the moderated mediation analyses confirmed that the indirect relationships between distributive, interactional justice and OCB through OI were valid for both high and low level of transactional contract, and only for low level of relational contract. Practical implications – To facilitate employees' OCB, organizations have to pay adequate attention to distributive justice which is rather neglected, and also must understand what types of psychological contract employees have. Originality/value – This study intensively explored the internal mechanism as to how the different types of organizational justice lead to OCB by identifying the mediating effect of OI and moderating roles of psychological contracts.